Przesłanki udziału organizacji ekologicznych w postępowaniach dotyczących ochrony środowiska w Polsce i w Niemczech - Maćkowiak, Karol (Studia Prawa Publicznego, 2024)
The article analyses the prerequisites for the participation of environmental organisations in administrative and administrative court proceedings in the field of environmental protection in Poland and Germany. There are significant differences between the two legal systems, despite the source of the broad powers of environmental organisations, including the right to initiate judicial review in cases involving other persons, deriving from the same act of international law the Aarhus Convention. In the scope in question, Polish regulations, established primarily in the Act of 3 October 2008 on the provision of information on the environment and its protection, public participation in environmental protection and environmental impact assessments, do not impose significant requirements on environmental organisations. In contrast, the German provisions, established primarily in the Gesetz über ergänzende Vorschriften zu Rechtsbehelfen in Umweltangelegenheiten nach der EG-Richtlinie 2003/35/EG, significantly restrict the access of environmental organisations to proceedings. The extended German solutions were treated as an inspiration to present de lege ferenda conclusions for the Polish legal order. The article points out the necessity of modifying Polish regulations towards limiting access of environmental organisations to administrative and judicial-administrative proceedings. In the author’s opinion, the prerequisites for the participation of environmental organisations should be more broadly linked to the rights they obtain. In other words, before allowing a given organisation to participate in the proceedings, the authority should examine such issues as, having at its disposal specialist knowledge, its previous activity, which is supposed to provide guarantees of proper performance of its statutory tasks. On the other hand, those German solutions which do not refer to the objectives of organisations’ participation in environmental proceedings do not merit implementation.